Avaliação do potencial de biossorção dos íons Cd (II), Cu (II) e Zn (II) pela macrófita Egeria densa - Pietrobelli, Juliana Martins Teixeira de Abreu (2007)
In the present work has been studied the metallic ion removal from aqueous solutions using the non-living aquatic macrophytes Egeria densa as biosorbent in order to assess its potential on cadmium, cuprum and zinc ions adsorption experiments. For this purpose, several adsorption tests were performed by duplicate in order to determine the optimal experimental conditions, based on the effects of aqueous solution pH, drying temperature, and particle size on mono-component adsorption kinetic and equilibrium experiments using the E. densa dry biomass. Metallic aqueous solutions were prepared dissolving cadmium, cuprum and zinc chlorate (Cl2Cd.H2O, Cl2Cu.2H2O, Cl2Zn) in deionized water. In this way, some biosorption experiments were carried out setting up aqueous solution pH values at 4, 5 and 6 and non-adjusted pH value under constant and controlled temperature at a shaker system for each metallic ion in order to obtain the equilibrium parameters. At each experiment, initial and final metal concentrations were determined by the Atomic Absorption Spectrometry technique. At room temperature and without shaking up, the metal precipitation into the aqueous solution was observed since pH 5 for cadmium and cuprum ions, while for zinc ion this process has began only near to pH 6. Based on the metallic ion removal factor at 30 and 50oC, the best biosorbent drying temperature was obtained at low temperature. On the other hand, the particle size effect onto metal biosorption process is not significant according the similar metallic removal factor for all the different particle sizes investigated. The biosorption kinetic results at non-adjusted pH and 5-adjusted pH and have shown an equilibrium time reduction from 60 to 45 and 30 minutes for cadmium and zinc ion, respectively. While, for cadmium ion, the pH effect was to reduce from 12 to 2 h due to change the aqueous solution pH value from non-adjusted to 5, respectively, with an increasing on removal factor from 60 to 70%. The experimental data were interpreted by four adsorption models. The pseudo first and second order models were used to fit the kinetic biosorption data. For all the metallic ions investigated the pseudo second order model has got fitting better the kinetic biosorption data. On the other hand, the Freundlich and Langmuir model were used to interpret the equilibrium data. For adsorption experiments at pH 5 and according to statistical criteria, the Langmuir model was better than Freundlich one to fit the experimental data. The adsorption parameters, qmax and b, obtained from Langmuir model were 1.28 mequivg-1 and 0.40 L g-1, 1.47 mequivg-1 and 3.73 L g-1, 0.922 mequivg-1 and 0.829 L g-1 for cadmium, cuprum and zinc, respectively. At mono-component biosorption conditions suggested above, the non-living aquatic macrófita E. densa biomass can be used into effluent treatment systems as biosorbent due to its great adsorption potential.